From mechanisms to therapies: current advances breakthroughs in alopecia areata immunopathology - Zhao, Huai-Bo; Zhang, Ya-Nan; Qiang, Yan; Wang, Guo-Mi; Wang, Li-Wei; Jiang, Wen-Cheng; Chen, Xi (Frontiers in Immunology, 2025)
Alopecia areata (AA) is a prevalent autoimmune condition characterized by hair loss, with the collapse of hair follicle immune privilege being a pivotal event in its pathogenesis. This collapse involves intricate immunological disturbances, where CD8+NKG2D+ T cells, driven by inflammatory cytokines like IFN-γ, attack hair follicles. Additionally, various immune cell, including Th1, Th2, Th17 cells, γδT cells, NK cells, and mast cells, contribute to this pathological process. Defects in the function of Tregs, Bregs, and iNKT cells further compound the immune imbalance. At the molecular level, the JAK-STAT pathway emerges as a central regulatory node integrating multiple cytokine signals and presenting itself as a significant therapeutic target. JAK inhibitors have shown notable effectiveness in clinical settings, with some agents even gaining FDA approval for treating moderate-to-severe AA. However, the effectiveness of targeting IL-17, TNF-α, Th2 cytokines, PDE4, and other molecules remains debated. This review comprehensively explores the dynamic interactions among immune cell subsets, cytokine networks, and crucial signaling pathways in AA pathogenesis. It also summarizes the latest clinical progress and challenges in targeted therapies. Future studies should delve deeper into AA’s immune regulatory framework and devise tailored treatment approaches to enhance patient outcomes.